Integration of Governance, Risk, and Compliance as Parameters for Determining Business Judgment Rules in Legal Protection Efforts for Directors - Tina Amelia; Mohamad Ismed (Universitas Islam Sultan Agung, 2026)
The purpose of this research is to examine the GRC integration as a normative and empirical parameter for the utilization of the doctrine of the Business Judgment Rule (BJR). The integration of GRC acts as a legal safeguard for the Board of Directors in state-owned enterprises (SOEs). This research will utilize the socio-legal approach and empirical qualitative method. Data collection will be done by conducting in-depth interviews and documentation at